Mitigating teacher professionalism problem in Indonesia: What Scopus AI tell us? - H. Husamah; Jazilah Azizah; Tutut Indria Permana; Yanur Setyaningrum; Iin Hindun (Jurnal Pendidikan Profesi Guru, 2025)
Teacher professionalism in Indonesia remains a central concern in educational reform, impacting the overall quality of education. Despite significant efforts through government initiatives, certification programs, and professional development schemes such as PPG and the Competence Test for Teachers, challenges persist. Limited access to training, inadequate workplace culture, and political resistance hinder effective reform. This study aims to analyze the current efforts, policy initiatives, contributing factors, and best practices addressing teacher professionalism in Indonesia. A comprehensive literature review, utilizing Scopus AI’s advanced search tools, was conducted to identify prevailing themes, challenges, and emerging trends. Key findings suggest that while initiatives like "kampus mengajar" and heutagogy-informed education models show promise, the success of these programs depends heavily on improved access to training, better school infrastructure, and overcoming bureaucratic barriers. The study concludes that a holistic approach integrating training, workplace culture reform, and technological tools is essential for enhancing teacher professionalism.